Supported liquid membrane for acetic acid extraction : screening of membrane support preparation factors - Siti Aisyah, Abdull Malid (2017)
Lignocellulosic materials can be acid hydrolyzed into fermentable sugars for ethanol production. However, inhibitory compounds such as carboxylic acid, furans and phenolic substances are also generated during this process. It is necessary to separate these inhibitors from the sugars or to reduce their concentration prior to the fermentation process in order to maximize the ethanol yields. This work focused on the removal of the acetic acid from biomass hydrolysate using supported liquid membrane (SLM) process. The membrane support for the SLM system was fabricated from 15wt% PES, 42.5wt% DMAc, 42.5wt% PEG 200 and 0.1wt% graphene by using vapour-induced phase separation (VIPS) method. Tri-n-octylamine (TOA) and 2-ethyl hexanol were used as carrier and solvent respectively in organic liquid membrane formulation. Two level full factorial design (FFD) was employed to perform the screening of three factors during VIPS process which are temperature of water bath (A) (30-60⁰C), exposure time (B) (10-60 seconds) and air humidity (C) (70-90%). The response was evaluated based on acetic acid extraction percentage from 10 g/L aqueous acetic acid feed solution. From the screening result, all three main factors were significant to the SLM performance. Air humidity factor (C) gave the highest contribution of 28.96% among the main factors. In term of the interaction between factors, water bath temperature (A) and exposure time (B) give the most significant effect with 45.01% percentage of contribution. The second highest interaction effect with 13.20% contribution was the interaction between air exposure time (B) and air humidity (C), however the interaction graph is not intercept. Meanwhile, the interaction effect of water bath temperature (A) and air humidity (C) is insignificant as extraction of acetic acid decrease as both factors were increased. The highest extraction percentage for the acetic acid using SLM system was 75.95% which is using the membrane prepare at 30⁰C water bath temperature, 10 seconds exposure time and 70% air humidity.